Strategi Pembelajaran Berbasis E-Learning Pada Warga Belajar Program Kesetaraan Paket C Kelas X Di SPNF SKB 1 Samarinda - Winarti, Hepy Tri; Wahyuni, Sri; Rinjani, Annisa Maharani; Adawiyah, Rabiatul Maharani (Peneliti.net, 2025)
At SPNF SKB 1, the learning program is based on e-learning in package c class X. Tutors and students must adapt to the use of media such as WhatsApp Group, Google Classroom, Youtube, Google Meeting And Zoom. Curriculum The ones used are curriculum 13 and KUMER (Independent Curriculum) because they are still making adjustments to the new curriculum. Tutors must have a learning strategy by making learning materials as creative as possible so that students become active, easy to understand and can improve their learning outcomes. The aim of the research is to analyze E-Learning Based Learning Strategies for Residents Studying the Package C Class X Equivalency Program at SPNF SKB 1 Samarinda. This research uses descriptive qualitative research to analyze the learning strategy process applied in e-learning package C. The results of the research are 1) E-learning learning methods: demonstration, inquiry, problem based learning (PBL), lecture, discussion; 2) E-learning learning media: Zoom, Google Meet, Google Form, Whatsapp, YouTube and SeTara Online; and 3) e-learning learning approach: contextual (CTL) and deductive. Tutors in e-learning learning strategies use various methods, media and approaches that are adapted to the learning material. The e-learning learning strategy in the Package C program can improve students' understanding and learning outcomes in achieving optimal learning goals from collaboration between tutors and students